A method to control the instability of a class of Laplace transform inversion algorithms - Therapos, C.P.; Diamessis, J.E. (Proceedings of the IEEE, 1983)
A simple method is presented for controlling the numerical instability, inherent in the Laplace transform inversion techniques, which are based on the truncation of Legendre function series expansions. A criterion characterizing the quality of the approximation is also proposed.